Family Caregivers, Patients and Physicians: Ethical Guidance to Optimize Relationships - Mitnick, Sheryl (Springer-Verlag, 2010)
Family caregivers play a major role in maximizing the health and quality of life of more than 30 million individuals with acute and chronic illness. Patients depend on family caregivers for assistance with daily activities, managing complex care, navigating the health care system, and communicating with health care professionals. Physical, emotional and financial stress may increase caregiver vulnerability to injury and illness. Geographically distant family caregivers and health professionals in the role of family caregivers may suffer additional burdens. Physician recognition of the value of the caregiver role may contribute to a positive caregiving experience and decrease rates of patient hospitalization and institutionalization. However, physicians may face ethical challenges in partnering with patients and family caregivers while preserving the primacy of the patient-physician relationship. The American College of Physicians in conjunction with ten other professional societies offers ethical guidance to physicians in developing mutually supportive patient–physician–caregiver relationships. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-009-1206-3) contains supplementary material, which is available to authorized users.